Pancreatic Exocrine Function and Methods of its Evaluation - N.V. Nagornaya; М.P. Limarenko (Zaslavsky O.Yu., 2012)
Physiology of pancreatic exocrine function is reflected in the article. Composition of pancreatic juice, stages of secretory cycle of acinar cells, phases of pancreatic secretion had been described. The methods of study of exocrine function of pancreas are presented.